Mendelian Randomization Reveals Potential Causal Relationships Between DNA Damage Repair-Related Genes and Inflammatory Bowel Disease - Zhihao Qi; Quan Li; Shuhua Yang; Chun Fu; Burong Hu (Biomedicines, 2025)
DNA damage repair (DDR) plays a key role in maintaining genomic stability and developing inflammatory bowel disease (IBD). However, no report about the causal association between DDR and IBD exists. Whether DDR-related genes are the precise causal association to IBD in etiology remains unclear. Herein, we employed a multi-omics summary data-based Mendelian randomization (SMR) approach to ascertain the potential causal effects of DDR-related genes in IBD. Methods: Summary statistics from expression quantitative trait loci (eQTL), DNA methylation QTL (mQTL), and protein QTL (pQTL) on European descent were included. The GWAS summarized data for IBD and its two subtypes, Crohn’s disease (CD) and ulcerative colitis (UC), were acquired from the FinnGen study. We elected from genetic variants located within or near 2000 DDR-related genes in cis, which are closely associated with DDR-related gene changes. Variants were selected as instrumental variables (IVs) and assessed for causality with IBD and its subtypes using both SMR and two-sample MR (TSMR) approaches. Colocalization analysis was employed to evaluate whether a single genetic variant simultaneously influences two traits, thereby validating the pleiotropy hypothesis. Results: We identified seven DDR-related genes (Arid5b, Cox5a, Erbb2, Ube2l3, Gpx1, H2bcl2, and Mapk3), 33 DNA methylation genes, and two DDR-related proteins (CD274 and FCGR2A) which were all causally associated with IBD and its subtypes. Beyond causality, we integrated the multi-omics data between mQTL-eQTL and conducted druggability values. We found that DNA methylation of Erbb2 and Gpx1 significantly impacted their gene expression levels offering insights into the potential regulatory mechanisms of risk variants on IBD. Meanwhile, CD247 and FCGR2A could serve as targets for potential pharmacological interventions in IBD. Conclusions: Our study demonstrates the causal role of DDR in IBD based on the data-driven MR. Moreover, we found potential regulatory mechanisms of risk variants on IBD and potential pharmacological targets.